Effect of the Pulsed Laser Energy on the Properties of CdO: NiO Composite Thin Films for Solar Cell Applications - Mahmood, Khamees D.; Aadim , Kadhim A.; Hammed , Mohammed G. (Iraqi Journal of Science, 2022)
In this work, thin films of cadmium oxide: nickel oxide (CdO: NiO) were prepared by pulsed laser deposition at different pulse energies of Nd: YAG laser. The thin films’ properties were determined by various techniques to study the effect of pulse laser energy on thin films’ properties. X-ray diffraction measurements showed a mixture of both phases. The degree of crystallinity and the lattice constant increase with the laser energy increase, while the lattice strain decreases. FE-SEM images show that the substrates’ entire surface is uniformly covered, without any cracks, with a well-connected structure consisting of small spherical particles ranging in size from 15 to 120 nm. Increasing the laser power causes to increase the particle size irregularly. EDX analysis showed increased oxidation in the samples using laser energy. The AFM of the thin film deposited at minimum energy shows the uniform deposition of samples prepared at the lowest energy. They are increasing pulses energy of the laser cause to increase in the average particle diameter and surface roughness. The charge carrier concentration decreases, and its mobility increases with laser energy. The I-V characteristics for CdO: NiO/porous-PSi heterojunctions prepared by different laser energies show photovoltaic properties. Optimum efficiency of the samples prepared with the lowest laser energy.